An innovated theory and closed form solutions for the elastic lateral torsional buckling analysis of steel beams/columns strengthened with symmetrically balanced GFRP laminates. (1st April 2022) - Van Pham, Phe
Highlights: 2 closed form solutions and 4 eigenvalue problems are developed for GFRP-strengthened steel beams. Partial interaction, GFRP shear deformations, GFRP stacking sequences are captured in the solutions. Buckling resistances of the present study are in excellent agreements with those of 3D FEA solutions. Effects of GFRP stacking sequences, thickness, elastic moduli on the buckling resistances are quantified. Effects of adhesive thickness and moduli on the buckling resistances are also quantified. Strengthened systems with GFRP fiber angles of ± 45 0 maximize the system buckling moments. Strengthened systems with GFRP fiber angles of 0 0, 90 0 have low buckling moments. Gains of buckling resistances for the systems strengthened with GFRP laminates are significant. Abstract: An innovated theory based on the principle of total stationary buckling energy is successfully developed for the elastic lateral torsional buckling analysis of steel beams/columns strengthened with symmetrically balanced GFRP laminates. Two closed form solutions and four eigenvalue solutions of the buckling resistances are then developed based on the theory and based on postulated buckling displacement functions. The present theory captures the partial interaction between the steel member and the GFRP laminates, stacking sequences and orthotropic properties of GFRP laminae, shear deformations in the GFRP laminates, and local and global warping deformations. The elastic buckling resistances predicted by the present solutions are well validated against those of three dimensional finite element analyses, as presented in three examples and two parametric studies of the present study. The present solutions are fast and convenient to predict the elastic buckling resistances of GFRP-strengthened beams/columns. Based on the parametric studies conducted, it is observed that the effects of GFRP lamina stacking sequences (with different fiber orientation angles), GFRP laminate thicknesses, GFRP moduli of elasticity, GFRP shear moduli, and adhesive shear moduli on the elastic buckling resistances are significant.